Analisis Makna Berbisnis dari Mahasiswa Business Incubator di Universitas - Puji Prabowo (STKIP PGRI SITUBONDO, 2023)
Business Incubators at universities aim to help students who have businesses to get good facilities and support in developing their businesses. This study aims to find out the meaning of doing business from students who are developing their business in one of the business incubators. It is important for business incubator managers to provide support and facilities according to the needs and wishes of business incubator members. This study uses a qualitative approach through an open-ended question survey of 87 students who are members of a business incubator at one of the universities in the city of Bandung. Data analysis used coding stages and cross tabulation using qualitative data analysis software to quantify qualitative data. The results of the study show that the most meaning of doing business for students is the meaning of success in doing business when the business has been recognized by many people, then it is sustainable for a long period of time, then it has a profit, and achieves the target of the business itself, as well as other meanings. This research is of practical use for business incubator managers to provide optimal service based on the needs of their members. In addition, this research theoretically helps in the development of knowledge about entrepreneurship education and management of business incubators.